2020
DOI: 10.5603/fm.a2019.0137
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the frequency of left renal vein variations in computed tomography and its relationship with cancer development

Abstract: Background: Left renal vein (LRV) variations occur in 0.8%-10.2% of the population.The most common LRV variations are retroaortic left renal vein (RLRV) and circumaortic left renal vein (CLRV). The purpose of this study is to determine the frequency of LRV variations in a large series on computed tomography (CT) and to investigate the association between LRV and malignancy development. examination of 12,341 (5,505 female, 6,836 male) patients was evaluated retrospectively in this study. Patients clinical and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…15 In a study where no statistically signi cant correlation was found between gender and variations of the LRV and CLRV, RLRV was found to be statistically signi cantly higher in men than in women (p = 0.039). 19 In the present study, no di erence was found between genders in terms of IVC and LRV variations.…”
Section: Discussioncontrasting
confidence: 56%
“…15 In a study where no statistically signi cant correlation was found between gender and variations of the LRV and CLRV, RLRV was found to be statistically signi cantly higher in men than in women (p = 0.039). 19 In the present study, no di erence was found between genders in terms of IVC and LRV variations.…”
Section: Discussioncontrasting
confidence: 56%
“…Another study reported an incidence of 1.7% of RLRV in cadavers [63]. Other studies reported prevalence of 1.84% and 6.6% for RLRV [66,68]. Cases of double RLRV have also been described [69,70].…”
Section: Retroaortic Left Renal Veinmentioning
confidence: 98%
“…The frequency of CLRV was 0.70%. Authors concluded that there was no difference in incidence of CLRV between women and men [66].…”
Section: Circumaortic Left Renal Veinmentioning
confidence: 98%
“…In ANCS, the LRV is compressed between the aorta and the superior mesenteric artery, whereas in PNCS, the LRV has a retroaortic course and is compressed between the aorta and vertebral column. Posterior NCS is the rarer of the two variants, with a prevalence of 0.77-1.56% (1,2).…”
Section: Introductionmentioning
confidence: 99%